Guidelines for public health and safety metrics to evaluate the potential harms and benefits of cannabis regulation in Canada. (2nd October 2019) - Lake, Stephanie; Kerr, Thomas; Werb, Dan; Haines‐Saah, Rebecca; Fischer, Benedikt; Thomas, Gerald; Walsh, Zach; Ware, Mark A.; Wood, Evan; Milloy, M.‐J.
Abstract: Issues: Canada recently introduced a public health‐based regulatory framework for non‐medical cannabis. This review sought to identify a comprehensive set of indicators to evaluate the public health and safety impact of cannabis regulation in Canada, and to explore the ways in which these indicators may be expected to change in the era of legal non‐medical cannabis. Approach: Five scientific databases were searched to compile a list of cannabis‐related issues of interest to public health and safety. A set of indicators was developed based on topics and themes that emerged. Preliminary evidence from other jurisdictions in the USA and Canada that have legalised medical and/or non‐medical cannabis (e.g. Colorado, Washington) was summarised for each indicator, wherever possible. Key Findings: In total, 28 indicators were identified under five broad themes: public safety; cannabis use trends; other substance use trends; cardiovascular and respiratory health; and mental health and cognition. Preliminary trends from other legalised jurisdictions reveal little consensus regarding the effect of cannabis legalisation on public health and safety harms and an emerging body of evidence to support potential benefits (e.g. reductions in opioid use and overdose). Implications: In addition to indicators of commonly discussed challenges (e.g. cannabis‐related hospitalisations, cannabis‐impaired driving), this review led to the recommendation of several indicators to monitor for possible public health and safety improvements. Conclusion: In preparing a comprehensive public health and safety monitoring and evaluation system for cannabis regulation, this review underscores the importance of not only measuring the possible risks but also the potential benefits.